Exergy-based entropy-generation analysis of electrodialysis desalination systems. (15th September 2020) - Generous, Muhammad M.; Qasem, Naef A.A.; Zubair, Syed M.
Highlights: Entropy generation analysis of electrodialysis cell pair shows various sources of entropy generation. The present method is more accurate than the literature method by about 20%. Ion exchange membranes contribution reaches 80% of the total entropy generation value. The diluate and concentrate channels could contribute to 16%. It is found that the optimal performance can be obtained at a channel width of 0.5–0.65 mm. Abstract: Entropy generation analysis is an important tool to evaluate the irreversible losses of the electrodialysis desalination system. Conventional entropy generation analysis of electrodialysis cell pair comprises of various sources of entropy generation. The primary sources were reported to be salt transport through ion exchange membranes, viscous losses, and pressure drop. In the present study, an exergy-based approach is implemented to calculate the maximum possible entropy generation rates (which was not addressed in the literature), in addition to current efficiency, voltage efficiency, and exergy efficiency. Unlike prior research, the present study calculated higher entropy generation rates (~20%) due to the accommodation of entropy generation from all the contributed sources. The exergy-based model is used to quantify entropy generation in various zones of the electrodialysis cell pair. The possible locations of entropy generation in a cell pair are found to be ion-exchange membranes, solutions, boundary layers, and so on. The membranes' contribution reaches 80% of the total entropy generation value, while the diluate and concentrate channels could contribute to 16%. The rest (~4%) is attributed to the boundary layers at the membrane-solution interfaces, while other sources are minimal. It is found that the optimal performance can be obtained at a channel width of 0.5–0.65 mm.